Analisis vegetasi Hutan Pura Taman Ayun, Kecamatan Mengwi, Badung, Bali - Rikhatul Jannah; Ni Wayan Utami (Jurnal Arsitektur Lansekap, 2025)
Pura Taman Ayun is one of the remaining historical relics of the former Mengwi Kingdom, located in Mengwi Village, Mengwi District, Badung Regency, Bali. The site features a forest situated to the north of the temple, currently functioning as a hydrological forest. Given its ecological significance, this study aims to analyze the diversity of vegetation which intended to serve as a guideline for the management and conservation Pura Taman Ayun forest area. A combination of observation, interviews, and literature review was employed, with research stages including data inventory, processing, and analysis. The forest was divided into four research plots, and vegetation was classified into four strata: trees, poles, saplings, and seedlings. The Shannon-Wiener Diversity Index (H') indicated that the diversity levels in the tree and seedling strata were moderate, while the pole and sapling strata showed low diversity. The highest Importance Value Index (IVI) was Mangifera indica for the tree stratum, Bambusa vulgaris for the pole stratum, Ptychosperma macarthurii for the sapling stratum, and Areca catechu for the seedling stratum. Based on the analysis, human activity and the adaptive capacity of vegetation may influence the high or low vegetation diversity in Pura Taman Ayun forest. Several rare species with low individual counts were also identified, highlighting the need for conservation planning to prevent extinction.